Production of ultrapure hydrogen in a Pd-Ag membrane reactor using noble metals supported on La-Si oxides. Modeling for the water gas shift reaction - Cornaglia, Carolina Andrea (2013)
Two different catalysts, Rh(0.6% wt/wt)/La2O3(27% wt/wt)·SiO2 and Pt(0.6% wt/wt)/La2O3(27%)·SiO2, were tested in the WGS reaction. Their performances were first studied in a conventional fixed-bed reactor. Their activities were similar and they were both very stable. However, as Pt(0.6)/La2O3(27)·SiO2 showed a much higher selectivity to the desired reaction, the performance of a membrane reactor employing this catalyst was studied. The effects of the H2O/CO ratio, space velocity, sweep gas flow rate and size of the catalyst particle on CO conversion and H2 recovery were studied at laboratory scale under isothermal conditions. A 1-D heterogeneous model was developed in order to properly reproduce the experimental results obtaining good agreement between the simulation results and laboratory data. The experimental and theoretical results confirm the existence of significant external mass-transfer limitations in the fluid-particle interface for these very active formulations.